Effect of Sitting Posture on Sit-Skiing Economy in Non-disabled Athletes - Lajunen, Kimmo; Rapp, Walter; Ahtiainen, Juha P.; Lindinger, Stefan J.; Linnamo, Vesa (Frontiers in Sports and Active Living, 2020)
This study focused on resolving the differences in economy between two common sit-skiing postures used by disabled athletes, suspected to be the most and least effective. Ten experienced non-disabled male cross-country skiers went through an incremental testing protocol with an ergometer simulating double poling in two sitting postures “kneeing” and “knee-high.” The protocol consisted of 3 × 4 min steady-state stages (13, 22, and 34% of maximal sprint power output). Subjects' respiratory gases and heart rate were measured and blood lactate concentrations were determined. In addition, pulling forces and motion capture recordings were collected. Oxygen consumption was 15.5% (p < 0.01) higher with “knee-high” compared to “kneeing” at stage three. At stage three cycle rate was 13.8% higher (p < 0.01) and impulse of force 13.0% (p < 0.05) and hip range of motion 46.6% lower (p < 0.01) with “knee-high” compared to “kneeing.” “Kneeing” was found to be considerably more economical than “knee-high” especially at 34% of maximum sprint power output. This might have been due to higher cycle rate, lower impulse of force and smaller hip range of motion with “knee-high” compared to “kneeing.” This indicates that sit-skiers should adopt, if possible, posture more resembling the “kneeing” than the “knee-high” posture. Combining such physiological and biomechanical measurements and to further develop them to integrated miniature wearable sensors could offer new possibilities for training and testing both in the laboratory and in the field conditions.